OPTIMASI FORMULA DAN UJI AKTIVITAS SECARA IN VITRO LOTION O/W SENYAWA KALKON SEBAGAI TABIR SURYA - Khansa Labibah; Abdul Karim Zulkarnain (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Chalcone is flavonoids class that have activity as sunscreen. The objective of this research is to find out the optimum formula of chalcone lotion, physical properties and stability of optimum formula lotion o/w, and sunscreen activity by spectrofotometry. The optimum formula was obtained by Simplex Lattice Design (SLD) method using Design Expert® version 10. To determine the optimum formula used three responses, namely viscosity, spreading, and adhessiveness. The physical properties of the lotion o/w were carried out including spreading test, adhessiveness test, and viscosity. The physical stability test of lotion o/w was done by cycling test. The sunscreen lotion activity o/w is determined by spectrophotometry by determining SPF, %Erythema Transmission, and %Pigmentation Transmission. Data were analyzed by t-test and One Way ANOVA with 95% confidence level. The results showed that the optimum lotion formula was found in combination of 2.40% cetyl alcohol, 0.36% carbopol, and 5.74% glycerin. The optimum formula of chalcone lotion has a viscosity of 73.48 ± 6.18 dPas, adhesiveness of 7.14 ± 1.26 seconds, and a spreading power of 24.99 ± 1.11 cm2. The results of statistical analysis showed that the lotion has a pretty good stability. Lotion has activity as sunscreen at concentration of chalcone in lotion 0,05% with SPF 36,927 and can provide protection against erythema and pigmentation.